Sustainable development in the era of digital trade: A perspective of industrial structure optimization - Zeyang Bian; Yaqian Zhang (Sustainable Futures)
Using panel data of prefecture-level cities in China from 2013 to 2020, we explore whether emerging digital trade can promote the high-quality development of the economy from the perspective of industrial structure optimization. Results show a positive impact of digital trade on industrial structure: a one-standard-deviation development of digital trade will lead to a 1.184-standard-deviation increase in the rationalization of industrial structure and a 1.558-standard-deviation increase in the upgrading of service industry structure. Our basic finding is confirmed with alternative specifications including a policy-based IV strategy, a quasi-natural experiment and a perspective of firm-level business scope, but varies across regional characteristics. Our study adds new insights into enacting digital trade-oriented place-based policies to optimize industrial structures and provides important implications for promoting high-quality economic and industrial development.